Of mice and hominins: using the craniomandibular morphology of hybrid mice to better understand hybrid morphologies in the Hominin fossil record - Warren, Kerryn Ashleigh (Department of Archaeology, 2017)
Since the sequencing of the Neanderthal genome in 2010, there has been an explosion of molecular research into hybridization and gene flow among hominin taxa in the Late Pleistocene. However, little research has focussed on how hybridization affects skeletal morphology. In regions and time periods where the recovery of ancient DNA is not possible, a thorough understanding of hybrid morphologies is essential for truly understanding hominin interactions in the past. This thesis examines the cranio-mandibular morphologies of hybrid mice across different degrees of phylogenetic relatedness (three sub-specific hybrids and one specific hybrid) and through several generations (F1s, B1s and F2s for the sub-specific hybrids), in order to build an animal model for better understanding hybrid morphologies. Cranio-mandibular size, form and shape are compared between parents and hybrids (N=634), as are frequencies of unusual non-metric traits. Morphometric analyses show that all first generation (F1) hybrids are intermediate in cranial and mandibular shape, and larger in size than the mid-parental mean, or sometimes even larger than parents. However, the expression of these differences in hybrids appears to be dependent on phylogenetic distances between parents, with sub-specific F1 hybrids often appearing transgressive (outside the range of both parents), and specific hybrids more intermediate. Subsequent hybrid generations (B1s and F2s) are highly variable in cranio-mandibular size and shape depending on the generation of the cross, possibly reflecting the degree of heterozygosity. B1s and F2s are highly variable, with examples of both parental morphologies as well as hybrid heterotic size being retained in some individuals. Models based on these data show that it is possible to detect hybridization in samples (as opposed to sampling sympatric non-hybridizing taxa) on the basis of morphological variability. In terms ofnon-metric cranial traits, hybrids are more likely to express unusual sutural anomalies and atypical bilateral foramina. Two specimens (intra-specific F1 and B1 individuals) showed extensive wormion bones. These data corroborate current research on hybrids, providing further evidence for the patterns seen in other animal hybrids. Furthermore, results of this study support morphological evidence for hybridization in several hominin specimens, including Oase II (cranium associated with a known multigenerational recombinant) and potentially other Middle Pleistocene hominins.